A geometria euclidiana na licenciatura em matemática do ponto de vista de professores formadores - Ramassotti, Luiz Carlos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research presents the view of a group of lecturers of undergraduate courses on how Euclidian Geometry should be approached in a Mathematics Degree Program, so that the graduating teacher has knowledge of geometry adequate for work on Middle and High School Education. The data collection method was questionnaire and interview, in which it is tried to identify the interviewee take on: rigor level of how axiomatization and formalization of geometry are presented, teaching strategies and how important the use of a ruler and compass is to the undergraduate formation of teachers. Taking into consideration modern technologies, it was also intended to highlight their opinions on the introduction to dynamic geometry softwares in Undergraduate Mathematics Education, specifically for the study of Geometry. The research sought to identify geometry textbooks that they consider adequate for the instruction of math teachers and pinpoint the reasons why there has been a neglect of geometry in Middle and High School classrooms. The interviewees shows that Euclidian Geometry must be presented in a strict axiomatic and formal way. In one demonstration the figure is an important teaching aid, being the demonstration justified by results and theorems already proven. Because of students lack of ability to comprehend the formal axiomatic system, it is suggested that geometry be studied closer to the end of courses to provide better understanding and knowledge retention. Ruler and Compass are found to be essential. Combined with important use of dynamic geometry sotware, these teachings aids will improve visualization and movement. The existing Brazilian Bibliography must be supplemented by foreign works, concluding that there is a need of reference works in this área in our country. The lack of specific knowledge and teaching tools is pointed as the reason for the absence of geometry in the Middle and High School classroom, problem originated in the ...

Esta pesquisa apresenta o ponto de vista e as opiniões que um grupo de professores formadores considera como deve ser abordada a Geometria Euclidiana em um curso de Licenciatura em Matemática para que o professor tenha uma formação geométrica adequada ao exercício da docência na Educação Básica. A coleta de dados se deu por meio de entrevistas semiestruturadas, procurando identificar as considerações dos entrevistados em relação a temas como o nível de rigor com que trabalham a axiomatização e formalização da geometria, das estratégias e da importância do uso da régua e do compasso e, no contexto atual das tecnologias, destacamos suas opiniões acerca da introdução dos softwares de geometria dinâmica na Licenciatura em Matemática, especificamente no caso da geometria. Identificamos, também, qual a literatura de geometria que é por eles utilizada ou considerada adequada na formação inicial do professor de matemática e apontamos suas opiniões sobre quais os motivos do abandono da geometria nas salas de aula da Educação Básica. Os entrevistados apontam que a Geometria Euclidiana deve ser trabalhada de forma axiomática e com formalização rigorosa, de modo que em uma demonstração a figura é um recurso didático, sendo as justificativas decorrentes de resultados e teoremas já demonstrados. Devido à imaturidade do aluno para entender o sistema axiomático formal, os depoentes sugerem que a geometria pode ser trabalhada mais para o final do curso, proporcionando melhor entendimento e ganho em relação ao conteúdo. Régua e compasso são considerados essenciais, e o software de geometria dinâmica, importante como recurso didático que facilita a visualização e movimentação. A bibliografia nacional existente seja complementada com obras estrangeiras, o que nos faz concluir que existe uma carência nesse setor em nosso país. Falta de conhecimento específico e...
Keywords: Professores - Formação; Geometria euclidiana; Geometria - Estudo e ensino; Euclidean geometry